The Fisher Separation Theorem And Capital Budgeting Decisions Of Quoted Firms In Nigeria - Olulu-Briggs, Omiete Victoria (Archives of Business Research, 2021)
This study explored the Fisher separation theorem and capital budgeting decisions of quoted firms on the Nigerian stock exchange. A sample of 60 questionnaires were filled and returned by staffs from particular sectors like manufacturing, health and agriculture. Descriptive statistics was employed to illustrate the data while the Spearman rank order correlation test was used to determine if a significant relationship exist among the variables. From the estimates, the Net Present Value and Modified Internal Rate of Return are regularly employed by firms in making capital budgeting decisions. Also, when firms employ capital budgeting tools, it creates wealth for both managers and shareholders, providing support for the Fisher’s separation theorem. Finally, a correlation coefficient of 0.827 reflect a positive and linear relationship between capital budgeting decision and Shareholders’ value creation. Thus, an increase in capital budgeting decisions result to an increase in value creation. This outcome is consistent with findings from other economies and previous studies. It thus recommends that firms in the Nigerian environment should ensure they play down on shareholders’ desire for dividends and instead redirect their funds to more investments by employing suitable capital budgeting decisions.